2012
DOI: 10.1093/europace/eus240
|View full text |Cite
|
Sign up to set email alerts
|

Lead vegetations in patients with local and systemic cardiac device infections: prevalence, risk factors, and therapeutic effects

Abstract: Lead vegetations were frequently observed in patients with only local symptoms. Therefore, TEE should be mandatory in all patients undergoing LE for infective indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
4
27
1
2
Order By: Relevance
“…The multivariate analysis demonstrated a significant relationship between elevated CRP and LDIE. In one of the few studies measuring inflammatory markers in LDIE, the ESR, CRP, and white blood cell count were elevated [25]. Another analysis of 44 patients with LDIE confirmed the significantly elevated ESR and white blood cell count in over 50 % of patients [13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The multivariate analysis demonstrated a significant relationship between elevated CRP and LDIE. In one of the few studies measuring inflammatory markers in LDIE, the ESR, CRP, and white blood cell count were elevated [25]. Another analysis of 44 patients with LDIE confirmed the significantly elevated ESR and white blood cell count in over 50 % of patients [13].…”
Section: Discussionmentioning
confidence: 95%
“…TEE in the present study detected vegetations in 60.0 % of patients. A recent observational study in 136 patients undergoing TLE for infective reasons demonstrated a similar location and frequency of vegetations in TEE [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Kilka czynników prognostycznych można dokładniej ocenić na podstawie TTE niż TEE, w tym obecność płynu w worku osierdziowym, zaburzenia funkcji komór i wartości ciśnień w krążeniu płucnym. TEE cechuje się większą czułością i specyficznością w odniesieniu do rozpoznania zapalenia wsierdzia związanego z elektrodami [381][382][383][384][385]. TEE pozwala zobrazować elektrody o nietypowej lokalizacji, np.…”
Section: Rozpoznanieunclassified
“…However, some studies have reported the prevalence of lead vegetation to be as high as 40%. 8,9 In addition, the risk of infection can increase up to tenfold if the patient is undergoing a lead replacement or a device upgrade. 10 Early infection refers to cases occurring the first month following the procedure.…”
Section: Epidemiologymentioning
confidence: 99%